The Impact of AUKUS in Indonesian Perspective: Regional Military Balance and Security Dilemma - Alifsar Nurfauzi; Frisca Lampita; Muhammad Rizky Mahendra (Jurnal Sentris, 2022)
Indonesia in issuing Australia’s plans to pursue nuclear-powered submarines and the launch of AUKUS as a new security grouping between Australia, the United Kingdom, and the United States aimed at promoting greater defense industry cooperation will be significant considerations for Indonesia. As one of Australia’s major neighboring country, one of Indonesia major concerns will be the significant impact on the region’s military balance. Not only will Australian nuclear-powered submarines will be able to undertake long-endurance, high-speed, stealth operations, but they could be equipped with upgraded missile systems. The Indonesian government viewed the submarine decision ‘cautiously’ and was ‘deeply concerned’ over the continuous arms race and power projection in the region. The aim of this paper is to analyze how Australia’s decision to power up its maritime capability create a security dilemma for Indonesia that left Indonesia ‘jammed’ between two major powers. This could increase the tension in the region. As Indonesia believe the AUKUS will provoke China into developing more sophisticated anti-submarine which would generate anxiety for Jakarta. This could lead into arms race between major powers.The author uses qualitative research to find fact and answer research questions on Indonesia’s concern regarding AUKUS will trigger China and provoke arm race in the region and create security dilemma for Indonesia.